Mapping wrist motion: 3D CT analysis after scapholunate ligament transection - Promny, Dominik; Gill, Dominik; Lyer, Stefan; Alexiou, Christoph; Buder, Thomas; Neuhuber, Winfried; Horch, Raymund E.; Arkudas, Andreas (Journal of Anatomy, 2024)
The injury of the scapholunate (SL) ligament is common in wrist traumas leading to pain and reduced wrist function. The wrist's unique joint design and possible underlying theories as the carpal row theory were subject to earlier investigations studying wrist kinematics. Nevertheless, a comprehensive understanding of how SL ligament injuries affect wrist biomechanics is still lacking. Through a quantitative analysis of carpal bone motion patterns, we evaluated the impact on wrist kinematics occurring after SL ligament injury. We conducted a study using computer tomography imaging to analyse wrist kinematics after SL ligament transection in 21 fresh-frozen anatomical specimens. The collected data were then transformed into 3D models, employing both standardized global and object coordinate systems. The study encompassed the evaluation of rotation and translation for each individual carpal bone, as well as the ulna, and all metacarpal bones in reference to the radius. The study showed a significant increase in rotation towards palmar (p < 0.01), particularly notable for the scaphoid, following transection of the SL ligament during palmar flexion. Ulnar deviation did not significantly affect rotation or translation, and radial deviation also showed no significant changes in rotation or translation. The study highlights the significance of the SL ligament in wrist kinematics, revealing that SL ligament tears lead to changes in wrist motion. While we observed significant rotational changes for the scaphoid, other carpal bones showed less pronounced alterations, emphasizing the complexity of wrist biomechanics.
CRIS-Team Scopus Importer:2024-08-09
Keywords: carpal bone motion; CT imaging analysis; scapholunate (SL) ligament injury; wrist biomechanics; wrist kinematics